2019
DOI: 10.1007/s11528-019-00467-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement Technology for Building a Sustainable OER Initiative in an Academic Library

Abstract: In keeping with its land grant mission, a university campus library partnered with several OER advocacy efforts on both national and state levels to promote the creation and use of OER at the university. While the program had some initial success in inspiring faculty to create and use OER in their courses, the effort proved difficult to sustain. This paper presents the application of the Performance Improvement/HPT model to an Open Educational Resources (OER) initiative in a university library. This paper focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Results based on micro-learning practices were key to the traditional classroom innovation. In this context, Nano-MOOC innovates traditional processes for enhanced academic performance [15], [11]; findings regarding the importance of learning environment designs from university students perspective validated the concept for better learning competencies applied to formal and informal educational processes [30].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Results based on micro-learning practices were key to the traditional classroom innovation. In this context, Nano-MOOC innovates traditional processes for enhanced academic performance [15], [11]; findings regarding the importance of learning environment designs from university students perspective validated the concept for better learning competencies applied to formal and informal educational processes [30].…”
Section: Resultsmentioning
confidence: 94%
“…Authors confirm that environmental educations support sustainable development objective-ODS-since it protects the natural environment, creates awareness and the innovation of revolutionary technological resources and also the creation of new learning environments offering new learning opportunities so that formal and informal education is supported [31], [10], [23], [30]; microlearning is taught by technological resources including key-topic short video-clips having the potential to enhance professional development and the innovation of traditional methodologies to improve academic performance [8], [15], [11].…”
Section: Introductionmentioning
confidence: 99%
“…When significant resources are required to sustain a program that results in limited output and cost savings for students, some libraries may determine that there is not a strong argument for continued OER publishing support (Morgan, 2018). Essmiller et al (2019) underwent a performance improvement process to develop a sustainable OER program; by establishing the OER program's alignment with the mission and values of the institution and by identifying gaps between the current and desired states of the program, they were able to secure support and resources that contribute to its long-term sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Publishing platforms are often an integral part of OER publishing programs in academic libraries, and the availability of such infrastructure contributes to the sustainability of a program (Essmiller et al, 2019). In a survey of 33 US higher education institutions, Nyland (2019) found that word processing tools were the most common technology used by faculty to author their own open textbooks, followed by the learning management system (LMS), Pressbooks and Web authoring tools, such as WordPress.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation